The Influence of Canva and PJBL on Elementary School Students' Learning Outcomes: A Literature Review - Cici Irawati; Tri Joko Raharjo; Bambang Subali; Nuni Widiarti (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
The rapid integration of digital tools in primary education necessitates a robust pedagogical framework to optimize student engagement. This study aims to systematically review the impact of Canva-based learning media combined with the Project-Based Learning (PjBL) model on the learning outcomes of elementary school students. Using a Systematic Literature Review (SLR) approach, 25 high-quality national and international journals were analyzed based on thematic relevance and methodological rigor. The findings indicate that Canva catalyzes visual literacy and student interaction, while the PjBL model fosters a constructive environment for the development of critical and creative skills. The synergy between these two components significantly enhances cognitive outcomes and 21st-century skills, including collaboration and problem-solving. This research contributes to the discourse on digital pedagogy by highlighting how visual-centric tools can bridge the gap between abstract concepts and project execution in early childhood education. Practically, this study provides a strategic framework for elementary teachers to design technology-integrated curricula that are both interactive and goal-oriented. Ultimately, the integration of Canva and PjBL offers a transformative strategy to elevate the quality of digital-based learning in elementary settings.